2021
DOI: 10.1261/rna.077404.120
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a bacterial three-hybrid assay through in vivo titration of an RNA–DNA adapter protein

Abstract: Non-coding RNAs regulate gene expression in every domain of life. In bacteria, small RNAs (sRNAs) regulate gene expression in response to stress and are often assisted by RNAchaperone proteins, such as Hfq. We have recently developed a bacterial three-hybrid (B3H) assay that detects the strong binding interactions of certain E. coli sRNAs with proteins Hfq and ProQ. Despite the promise of this system, the signal-to-noise has made it challenging to detect weaker interactions. In this work, we use Hfq-sRNA inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…1 B); the strength of an RNA–protein interaction correlates to the fold-stimulation in β-gal activity over basal levels when all components are present ( Fig. 1 C; Wang et al 2021 ; Stockert et al 2022 ).…”
Section: Methodsmentioning
confidence: 91%
“…1 B); the strength of an RNA–protein interaction correlates to the fold-stimulation in β-gal activity over basal levels when all components are present ( Fig. 1 C; Wang et al 2021 ; Stockert et al 2022 ).…”
Section: Methodsmentioning
confidence: 91%
“…Reporter cells encode a lacZ reporter gene downstream of a test promoter on a single-copy Fʹ episome. Transformation of reporter cells with all three plasmids (pPrey, pAdapter, and pBait) leads to a boost in β-gal levels relative to basal levels indicated by three negative controls in which half of each hybrid component is left out (Fig 1B); the strength of an RNA-protein interaction correlates to the fold-stimulation in β-gal activity over basal levels when all components are present (Fig 1C; (Wang et al 2021;Stockert et al 2022)).…”
Section: Methodsmentioning
confidence: 98%
“…While there is substantial potential in the B3H assay, its current utility has been limited by only a modest success rate in detecting established RNA-protein interactions. Improvements in the expression level of adapter protein have increased signal for several Hfq-sRNA interactions with KD values out to ~100 nM (Wang et al 2021). Despite this progress, many well-characterized Hfq-sRNA interactions are undetectable in the current B3H assay.…”
Section: Introductionmentioning
confidence: 99%
“…While the original pBait constructs contained two copies of the MS2 hp (Berry and Hochschild 2018;Wang et al 2021), a single MS2 hp has been shown to be sufficient for detection of Hfq-sRNA interactions and, indeed, is critical for accurate detection of ProQ-RNA interactions (Pandey et al 2020). Due to its simplicity and broader applicability, we chose to focus our optimization of RNA display here on the 1xMS2 hp pBait construct.…”
Section: Introduction To Bacterial Three-hybrid Assaymentioning
confidence: 99%
See 1 more Smart Citation